Pesantren Management in Preserving Salafiah Pesantren Traditions in the Digital Age - Ina Nurwahidah; Devi Silvia Dewi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This study aims to analyze the management of Pesantren Miftahul Huda Karangsalam Parigi and its efforts to preserve the traditions of salafiyah Islamic boarding schools in the digital era. The focus is on how management functions are implemented and how classical educational traditions are maintained amid technological developments. A qualitative approach with a descriptive method was employed. Data were collected through observation, in-depth interviews, and documentation, while the data analysis followed Miles and Huberman’s model consisting of data reduction, data display, and conclusion drawing. The validity of the data was tested using triangulation of sources, techniques, and time. The findings reveal that pesantren management is carried out in a participatory manner, emphasizing collective deliberation, role modeling, and moral-based supervision. Salafiyah traditions such as the teaching of classical Islamic texts (kitab kuning), and learning methods including sorogan, bandongan, and halaqah are preserved, although limited adaptation to digital technology has been introduced. This indicates that the pesantren successfully maintains a balance between traditional values and modern needs. The originality of this study lies in its depiction of a contextual management model for salafiyah pesantren in the digital era. The results are expected to enrich the literature on Islamic education management and serve as a practical reference for other pesantren in sustaining traditions while responding to modernization.